Penerapan Green Economy dalam Pengelolaan Limbah Pertanian di Ambon - Arizal Hamizar; Fadli F. Malawat; Jaczy Tubalawony; Afdhal Yaman; Fatmah Watty Pelupessy (Journal of Business Application, 2024)
This study aims to analyze the application of green economy principles in agricultural waste management in Ambon City, focusing on the potential for improving farmers' welfare and its impact on environmental sustainability. The research employs a qualitative approach, utilizing depth interviews and observations with farmers in Ambon. This study involves farmers engaged in coconut, cocoa, and other agricultural practices, as well as communities that have begun implementing green economy principles in agricultural waste management. The results show that while most farmers in Ambon still rely on conventional waste management methods, a small number of farmers have successfully transformed agricultural waste into value-added products, such as compost and briquettes. This waste processing has positive impacts on both increasing farmers' income and reducing environmental impact. However, the greatest challenges faced are the lack of knowledge, training, and market access for eco-friendly products.